2021
DOI: 10.2196/26953
|View full text |Cite
|
Sign up to set email alerts
|

Tweet Topics and Sentiments Relating to COVID-19 Vaccination Among Australian Twitter Users: Machine Learning Analysis

Abstract: Background COVID-19 is one of the greatest threats to human beings in terms of health care, economy, and society in recent history. Up to this moment, there have been no signs of remission, and there is no proven effective cure. Vaccination is the primary biomedical preventive measure against the novel coronavirus. However, public bias or sentiments, as reflected on social media, may have a significant impact on the progression toward achieving herd immunity. Objec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
177
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(195 citation statements)
references
References 83 publications
11
177
1
6
Order By: Relevance
“…In general, existing studies have investigated people’s reactions towards COVID-19 vaccines, with a geographical emphasis on the United States [ 14 - 19 ]. Some papers have also studied other countries in the world, including China [ 20 ], South Africa [ 21 ], Australia [ 22 ], the United Kingdom [ 14 , 23 ], Canada [ 24 ], and Africa [ 25 ], and to a global scale [ 26 ]. However, the study period of these works is relatively limited to or predominantly focused on the early stage of the pandemic or up to the end of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In general, existing studies have investigated people’s reactions towards COVID-19 vaccines, with a geographical emphasis on the United States [ 14 - 19 ]. Some papers have also studied other countries in the world, including China [ 20 ], South Africa [ 21 ], Australia [ 22 ], the United Kingdom [ 14 , 23 ], Canada [ 24 ], and Africa [ 25 ], and to a global scale [ 26 ]. However, the study period of these works is relatively limited to or predominantly focused on the early stage of the pandemic or up to the end of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…As a major social media platform and a pivotal source for text based public discourse, Twitter has been studied to understand public reactions during various public health crises, including the Covid-19 pandemic (e.g. Abd-Alrazaq et al, 2020;Doogan et al, 2020;Kwok et al, 2021;Liu et al, 2020). Research on the role of Twitter in face of public health crises has focused on two directions: (a) Twitter as an information source for emergency responses management and (b) Twitter as the collective outcome for public perceptions and attitudes about health and risk issues.…”
Section: Topic Modeling For Social Media Discourse During Public Health Crisesmentioning
confidence: 99%
“…While most research identified general topics related to the COVID-19 outbreak such as origin, prevention, and impact (e.g. Abd-Alrazaq et al, 2020;Liu et al, 2020), only a few focused on non-pharmaceutical interventions (NPIs) (Doogan et al, 2020) or vaccination (Kwok et al, 2021). Therefore, we intended to study Twitter discourse on two preventive measures: mask-wearing and vaccination, with a particular focus on the United States, where the highest number of confirmed cases and deaths were confirmed (John Hopkins Coronavirus Resource Center, n.d.), and unsatisfactory compliance rate for mask-wearing (Igielnik, 2020, June 23, June 23) and moderate hesitancy level for vaccination were revealed in earlier surveys (O'Keefe, 2020, Aug. 7, August 7).…”
Section: Topic Modeling For Social Media Discourse During Public Health Crisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, user locational information enables researchers to investigate the spatiotemporal patterns of the public’s opinions and attitudes. In general, existing studies have investigated people’s reactions towards COVID-19 vaccines, with a heavy focus on the US [10-15] and also extends to other countries in the world, including China [16], South Africa [17], Australia [18], United Kingdom [19-20], Canada [21, 11], Africa [22] and to a global scale [23]. However, the study period of these works is relatively limited to or predominantly focused on the early stage of the pandemic or up to the end of 2020, without covering early 2021, the period of mass systemic vaccine implementation in many countries.…”
Section: Introductionmentioning
confidence: 99%